2010
DOI: 10.1007/s00417-010-1440-8
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab vs. sham treatment in acute branch retinal vein occlusion with macular edema: results at 3 months (Report 1)

Abstract: In acute BRVO, two IVB injections resulted in significant improvement of vision and CMT at 6 weeks relative to the sham group. However, the visual improvements in the IVB group were not significantly different from those in the sham group at 12 weeks. IVB injections accelerate an initial improvement of visual acuity but do not have any significant effects on vision after 12 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 35 publications
1
27
0
2
Order By: Relevance
“…It has been shown that VEGF is a key factor for macular edema in retinal vein occlusion [20,21], Therefore, inhibition of VEGF should theoretically offer a therapeutic benefit for BRVO. This effect has been shown with anti-VEGF drugs such as bevacizumab [8][9][10][11][12][22][23][24], ranibizumab [25,26], and pegaptanib [27] in terms of both VA improvement and CMT reduction. However, there are some concerns about their safety and their adverse effect on macular perfusion.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been shown that VEGF is a key factor for macular edema in retinal vein occlusion [20,21], Therefore, inhibition of VEGF should theoretically offer a therapeutic benefit for BRVO. This effect has been shown with anti-VEGF drugs such as bevacizumab [8][9][10][11][12][22][23][24], ranibizumab [25,26], and pegaptanib [27] in terms of both VA improvement and CMT reduction. However, there are some concerns about their safety and their adverse effect on macular perfusion.…”
Section: Discussionmentioning
confidence: 91%
“…Instead of the usual dosage of IVT (4 mg) [39,40], we administered 2 mg in order to reduce the side-effects of the drug. Most studies demonstrated a temporary beneficial effect of both IVB [20,22,41] and IVT [20,31,37,41] [31]. Because of these reported recurrences after intravitreal injections, we planned a prescheduled repeated therapy for both drugs.…”
Section: Discussionmentioning
confidence: 97%
“…BRVO usually occurs at an arteriovenous crossing and the degree of macular involvement determines the level of visual impairment, which may result from ischemic damage and/or secondary macular edema. Macular edema is common in eyes affected by BRVO (5-15 % in 1 year), and represents the most common cause of vision loss in these patients [4,5]. Treatment modalities for BRVO-associated macular edema have been mainly limited to retinal laser photocoagulation (grid pattern and sector scatter) and/or intravitreal corticosteroids for the past few years [6].…”
Section: Introductionmentioning
confidence: 99%
“…Early-phase CTs (phases I/II and III) showed a significant increase over time in the use of biomarkers for patient selection and stratification (including predictive, diagnostic Although 30 of 59 (50.8%) of phase III CTs used secondary surrogate imaging endpoints, we found only 3 of 59 (5.1%) phase III CTs including primary surrogate imaging endpoints: two on retina 16,17 (macular thickness by optical coherence tomography [OCT] and lesion enlargement by fundus autofluorescence) and one on glaucoma 18 (iris color photography). Conversely, phase IV CTs included primary surrogate imaging endpoints in 75 of 275 (27.2%) cases; P < 0.001.…”
Section: Thementioning
confidence: 50%